2020
DOI: 10.1002/htj.21903
|View full text |Cite
|
Sign up to set email alerts
|

Productivity enhancement of traditional solar still by using sandbags of El Oued, Algeria

Abstract: This manuscript aims to study the experimental analysis of solar still with sandbags as energy storage materials. To achieve this idea, 25 bags filled with El Oued sand was fixed inside a square basin vertically and distributed regularly, this is called the modified solar still with sandbags (MSS-SB). The sand used in this study is very effective than many store mediums considered within many previous works such as glass balls, sponges, phosphate, yellow sand, black sand, and black gravel. This fact is due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Gholizadeh and Farzi (Gholizadeh and Farzi 2020) analysed the still with sand as thermal storage, the results showed that the productivity was increased by 21.16 % relative to still without any thermal storage. Attia et al (Attia et al 2021) experimentally investigated the El Oued sandbags of 25 numbers, the results showed a 34.83 % increase in productivity. Arunkumar et al (Arunkumar et al 2020) experimentally investigated the solar still with different sensible storage materials such as spherical clay balls, Polyvinyl Alcohol sponges, pebbles and absorber plates coated with copper oxide nanoparticles.…”
Section: Sensible Thermal Storagementioning
confidence: 99%
“…Gholizadeh and Farzi (Gholizadeh and Farzi 2020) analysed the still with sand as thermal storage, the results showed that the productivity was increased by 21.16 % relative to still without any thermal storage. Attia et al (Attia et al 2021) experimentally investigated the El Oued sandbags of 25 numbers, the results showed a 34.83 % increase in productivity. Arunkumar et al (Arunkumar et al 2020) experimentally investigated the solar still with different sensible storage materials such as spherical clay balls, Polyvinyl Alcohol sponges, pebbles and absorber plates coated with copper oxide nanoparticles.…”
Section: Sensible Thermal Storagementioning
confidence: 99%
“…The scientists noticed that the output of the CSS with phosphate bags at 1 and 2 cm depth of basin water was 28 and 22.5% higher, respectively, when related to the CSS. Attia et al ( 2021e ) experimentally placed twenty-five sandbags as energy storage materials in CSS and compared their performance with the CSS throughout the day. The outcome showed that the yield productivity is 5060 ml/m 2 when sandbags were used, and 3760 ml/m 2 by CSS.…”
Section: Introductionmentioning
confidence: 99%
“…Many challenges and problems have recently afflicted the Earth, making it difficult to live on it. One of these issues is global warming, which is caused by increased carbon dioxide diffusion rates in the atmosphere as a result of fossil fuels [1][2][3][4][5]. Increased public awareness of the environmental risks posed by global warming, as well as fluctuating oil prices and dwindling global fossil fuel reserves, have prompted governments to turn to alternative energy sources to meet their energy needs in a clean, efficient, renewable, and long-term manner [6].…”
Section: Introductionmentioning
confidence: 99%